2019
DOI: 10.3390/molecules24132454
|View full text |Cite
|
Sign up to set email alerts
|

Veronica Plants—Drifting from Farm to Traditional Healing, Food Application, and Phytopharmacology

Abstract: The Veronica genus, with more than 200 species, belongs to the Plantaginaceae family and is distributed over most of the Northern Hemisphere and in many parts of Southern Hemisphere. These plants are traditionally used in medicine for wound healing, in the treatment of rheumatism, and in different human diseases. This paper reviews the chemical composition of some valuable Veronica species, the possibilities Veronica extracts have in food preservation and as food ingredients, and their functional properties. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 80 publications
0
72
0
Order By: Relevance
“…The ability of oleuropein to inhibit prooxidative processes has been shown in vitro on human LDL and on Caco-2 cells [149]. A large body of research has supported the in vitro cardioprotective potential of berry fruits rich in flavonoids, through improvements in plasma lipids and vascular function as well as systemic and vascular inflammatory response reduction [150,151]. LDL oxidation inhibition and induction of LDL receptor expression in hepatocytes have been demonstrated by cranberries consumption [152].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The ability of oleuropein to inhibit prooxidative processes has been shown in vitro on human LDL and on Caco-2 cells [149]. A large body of research has supported the in vitro cardioprotective potential of berry fruits rich in flavonoids, through improvements in plasma lipids and vascular function as well as systemic and vascular inflammatory response reduction [150,151]. LDL oxidation inhibition and induction of LDL receptor expression in hepatocytes have been demonstrated by cranberries consumption [152].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Neuroinflammation is a factor that plays an essential role in the increased loss of neuronal tissue and brain damage in cerebral ischemia, as well as in inflammatory diseases of the central nervous system (CNS) ( Table 1). For example, neuronal damage due to the accumulation of Aβ, tau protein and α-synuclein results in the recruitment and activation of microglia, which initiates the inflammatory response [43,79,80]. Cerebral ischemia and reperfusion injury (CI/RI) trigger the recruitment of resident microglia as well as infiltrating macrophages and neutrophils, which is followed by an enhanced inflammatory response and an over-production of inflammatory mediators (cytokines) [81,82].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Genistein is capable of attaching itself to the receptive proteins of the female sex hormones and having estrogen-specific hormonal effects, even being able to replace them, triggering either an estrogenic or a regulatory hormonal impact [85]. To date, studies have shown that the anti-inflammatory activity of curcumin, genistein, resveratrol and naringenin are arbitrated via the inhibition or downregulated translocation of nuclear factor-κB (NF-κB), which regulates the transcription of cytokines [80]. Ginsenosides [49], linalool [54], quercetin [57], resveratrol [53] and sulforaphane [74] inhibit pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β, IL-6 and IL-8 to reduce neuroinflammation in neurodegenerative models.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is crucial for both neurons' development and survivaland for synaptic plasticity. Polyphenols play a beneficial role in maintaining brain health [23]. They are potent antioxidants, and their presence in the diet decreases the markers of oxidative stress, which reduces the risk of neurological diseases [24].…”
Section: Introductionmentioning
confidence: 99%